2017
DOI: 10.1155/2017/2353240
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk with Inflammatory Macrophages Shapes the Regulatory Properties of Multipotent Adult Progenitor Cells

Abstract: Macrophages and microglia are key effector cells in immune-mediated neuroinflammatory disorders. Driving myeloid cells towards an anti-inflammatory, tissue repair-promoting phenotype is considered a promising strategy to halt neuroinflammation and promote central nervous system (CNS) repair. In this study, we defined the impact of multipotent adult progenitor cells (MAPC), a stem cell population sharing common mesodermal origin with mesenchymal stem cells (MSCs), on the phenotype of macrophages and the recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…In line with these studies, we previously demonstrated that muramyl dipeptide (MDP), a constituent of the bacterial cell wall, plays a crucial role in promoting the immunomodulatory mechanism of hUCB-MSCs, and preconditioning with MDP significantly augmented the therapeutic efficacy of hUCB-MSCs against experimental colitis 25. The crosstalk between the risk factors of a particular disease, including dysregulated activation of immune cells, and MSCs can be employed to identify its mode of action and develop disease-specific stem cell therapy 26. In the present study, we have suggested priming with MC granules as a possible approach to enhancing stem cell-based therapy aimed at reducing skin inflammation and tissue degeneration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these studies, we previously demonstrated that muramyl dipeptide (MDP), a constituent of the bacterial cell wall, plays a crucial role in promoting the immunomodulatory mechanism of hUCB-MSCs, and preconditioning with MDP significantly augmented the therapeutic efficacy of hUCB-MSCs against experimental colitis 25. The crosstalk between the risk factors of a particular disease, including dysregulated activation of immune cells, and MSCs can be employed to identify its mode of action and develop disease-specific stem cell therapy 26. In the present study, we have suggested priming with MC granules as a possible approach to enhancing stem cell-based therapy aimed at reducing skin inflammation and tissue degeneration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers demonstrated that MSCs skew monocytes towards an anti-inflammatory phenotype, thereby facilitating Treg differentiation 78 . MAPC cells have also been demonstrated to induce a comparable anti-inflammatory phenotype on myeloid cells in vitro 55 and in vivo 18 , however, the effect of MAPC cells on CD14 + monocytes responsible for their involvement in MAPC-mediated induction of Tregs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has shown that the behavior of MSCs has immunoregulatory potential following activation by macrophages [76,77] efficaciously deliver CCL2 secreted by human MSCs, which acts a part in not only recruiting macrophages but also driving their transformation to an M2 neuroprotective phenotype, to preserve motor neurons and myelin in the lesion [92].…”
Section: Communication Between Macrophages and Mscsmentioning
confidence: 99%